Medetnični odnosi v slovenskem etničnem prostoru - Nećak Lük, Albina (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1993)
The concept of the research project on relations between different ethnicities is presented in the article. A longitudinal multi- and interdisciplinary research is consacrated to the identification of the national identity indicators in the nationally mixed areas on both sides of the Slovene border, i.e.: in Slovenia, Austria, Italy and Hungary. In the first phases a questionary was applied to the members of the majority and the minority population in the town of Lendava/Lendva in Slovenia and Monošter/Szentgotthard in Hungary.
Keywords: etnična identiteta; etnični odnosi; Madžari; narodne manjšine; porabski Slovenci; Prekmurje; Slovenija